2012
DOI: 10.1179/1743281211y.0000000069
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion characterisation for clean steelmaking and quality control

Abstract: Improving steelmaking and casting processes to adapt to the requirements of internal and external customers involves continuous monitoring and evaluation of existing and development of new steel refining practices. Internal quality control of semifinished products requires tools that can correlate product defects to process anomalies. This article focuses on use of techniques such as measurement of complete steel and slag chemistry, inclusion analysis, process analysis and thermodynamics to assess the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Currently, many studies have been conducted to explore the effects of the inclusions on the machinability of the non-quenched and tempered steel [6][7][8][9][10][11][12][13][14]. Studies have shown that the sulfide in the steel mainly exists in the form of MnS [15], one of most harmful inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many studies have been conducted to explore the effects of the inclusions on the machinability of the non-quenched and tempered steel [6][7][8][9][10][11][12][13][14]. Studies have shown that the sulfide in the steel mainly exists in the form of MnS [15], one of most harmful inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…% P-content, is expected to be a substitute of steel scrap in electric arc furnaces (EAF) for steelmaking. It is well known that the phosphorus content of the feed stock for steelmaking must be strictly controlled because too high phosphorus content will cause cold brittleness and reduce the ductility brittleness of steel [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the hydrogen content in steel was measured on selected heats after completion of heat processing at Stirring Station and subsequently the hydrogen content was measured during their casting in the tundish using the movable Hydris ® -Lab analyser from Heraeus Company. To study the inclusions in the steelmaking process and final products, techniques are being developed to rapidly identify inclusions in steel [7,8]. Understanding the origin of inclusions and developing practices to control their composition and content in liquid steel are key point for optimization of production processes and parameters [9,10].…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%